Pelatihan Perancangan Website Untuk Siswa SMK Global Persada Mandiri Bekasi - Hartanti, Dian; Hafizah, Hafizah (Lembaga Penelitian, Pengabdian kepada Masyarakat dan Publikasi Universitas Bhayangkara Jakarta Raya, 2022)
The development of technological progress is currently very rapid because most human activities cannot be separated from information technology. Especially during the current Covid-19 pandemic, almost all community activities have shifted from offline to online, forcing people to be technology literate, one of which is the website. The increasing number of people's needs for information systems, and database processing, causing the creation of websites is increasingly needed. Therefore, the Faculty of Computer Science, University of Bhayangkara Jabodetabek supports SMK Global Persada Mandiri Bekasi to provide training to its students to increase competitiveness in the community and students are expected to have expertise in making website designs so that they can generate income by creating websites.